2011
DOI: 10.1371/journal.pone.0024014
|View full text |Cite
|
Sign up to set email alerts
|

The Lipid-Sensor Candidates CD36 and GPR120 Are Differentially Regulated by Dietary Lipids in Mouse Taste Buds: Impact on Spontaneous Fat Preference

Abstract: BackgroundRecent studies in rodents and humans suggest that the chemoreception of long-chain fatty acids (LCFA) in oral cavity is involved in the spontaneous preference for fatty foods and might contribute to the obesity risk. CD36 and GPR120 are LCFA receptors identified in rodent taste bud cells. The fact that CD36 or GPR120 gene inactivation leads to a decrease in the preference for lipids raises the question of the respective role(s) played by these gustatory lipid-sensor candidates.Methodology/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
142
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(166 citation statements)
references
References 26 publications
(48 reference statements)
17
142
3
1
Order By: Relevance
“…Consistent with this assumption, it was reported that the GLP-1 signaling modulates the sweet taste sensitivity ( 35 ). We recently reported that CD36 protein levels in mouse CVP is subjected to a highly sensitive short-term downregulation during food intake, in contrast to GPR120 ( 11 ). This regulation is strictly dependent on the presence of lipids in the diet.…”
Section: Downloaded Fromsupporting
confidence: 64%
See 2 more Smart Citations
“…Consistent with this assumption, it was reported that the GLP-1 signaling modulates the sweet taste sensitivity ( 35 ). We recently reported that CD36 protein levels in mouse CVP is subjected to a highly sensitive short-term downregulation during food intake, in contrast to GPR120 ( 11 ). This regulation is strictly dependent on the presence of lipids in the diet.…”
Section: Downloaded Fromsupporting
confidence: 64%
“…In contrast, GPR120 was systematically detected in murine and human gustatory papillae ( 11,15,18 ) in which it was frequently coexpressed with CD36 ( 11,19 ). This last observation raises the question of the respective role(s) of these two LCFA receptors in the coding mechanisms eliciting the oro-sensory detection of dietary lipids at the periphery.…”
Section: Licking Testsmentioning
confidence: 97%
See 1 more Smart Citation
“…CD36 has been reported as a key factor in innate immunity and phagocytosis in resolution phase after ischemic stroke (9). In addition, CD36 uptakes long chain fatty acids and oxidized lipids, and has been identified as a fat sensing gustatory receptor in the taste buds (10)(11)(12). CD36 is also highly expressed in the duodeno-jejunum of small intestine, the main site of fat absorption (13).…”
Section: Introductionmentioning
confidence: 99%
“…A 19) and Laugerette et al 21) and Martin et al 34) have found no preference for fatty acids in CD36-deficient mice. These findings suggest the chemoreception of dietary fat via CD36 in the oral cavity.…”
Section: Discussionmentioning
confidence: 96%